2012
DOI: 10.1016/j.jval.2012.08.1823
|View full text |Cite
|
Sign up to set email alerts
|

PHS50 Health Care Resource Use and Cost in Alzheimer's Disease in Three European Countries – Baseline Findings of the GERAS Study

Abstract: RUD) instrument. 2010 unit costs per country were applied. RESULTS:The study cohort included 1497 AD patients (38% mild, 32% moderate and 31% severe AD) and their caregivers (nϭ419 France, nϭ552 Germany and nϭ526 UK) with a mean (SD) patient age of 79.4 (6.8) France, 75.2 (7.6) Germany, 78.5 (7.8) UK and 62% females in France, 50% Germany, 54% UK. One or more nights in hospital were recorded for 4% of patients in France, 7% Germany, 1% UK. One or more outpatient visits (including GP visits) were recorded for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 47 studies reported economic data on the direct and indirect costs of AD for the seven selected countries; the remaining five studies reported aggregated international data [50][51][52][53][54]. Among the 47 studies, 17 primary source articles were identified in which cost component data were available and presented according to AD severity or patients' living conditions; two for France [55,56], four for Germany [7,[57][58][59], zero for Italy, three for the Netherlands [8,51,60], four for Spain [49,[61][62][63], two for the UK [64,65], and two for the USA [9,66].…”
Section: Economic (Direct and Indirect Costs)mentioning
confidence: 99%
“…A total of 47 studies reported economic data on the direct and indirect costs of AD for the seven selected countries; the remaining five studies reported aggregated international data [50][51][52][53][54]. Among the 47 studies, 17 primary source articles were identified in which cost component data were available and presented according to AD severity or patients' living conditions; two for France [55,56], four for Germany [7,[57][58][59], zero for Italy, three for the Netherlands [8,51,60], four for Spain [49,[61][62][63], two for the UK [64,65], and two for the USA [9,66].…”
Section: Economic (Direct and Indirect Costs)mentioning
confidence: 99%